العوامل المؤثرة في تشكيل مرفولوجيةالقصور قصور منطقة وادي ريغ نموذجا (مجلة الواحات للبحوث والدراسات, 2015)
The human is the son of his environment.He tried over time to adapt to natural conditions and overcome the hard knocks through finding and exploiting all disposed of in the various aspects of his life, and the desert castles in Algeria is a model for engineering innovation that has evolved over its long history, forming a distinct architectural proved human desert ability in planning and exploitation of available building materials using building techniques , architectural elements and artistic motifs. natural factors, religious and social factors clearly affect this architectural structure in many ways. That's what we'll try to discuss in detail through " OUED RIGH " Castles as a model.